Reverse coating BaCe1-xGdxO3-delta (at) Ce1-xGdxO2-delta core-shell structure composite ceramic and preparation method thereof
By reverse coated BaCe1-xGdxO3-δ@Ce1-xGdxO2-δ core-shell structure complex-phase ceramics, the problem of low reaction and sintering density of BaCeO3-based ceramics in air is solved, and a material preparation with high conductivity and high density is achieved.
Patent Information
- Application Number
- CN202510030035.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2045-01-08
AI Technical Summary
The existing BaCeO3-based ceramics are prone to react with H2O and CO2 in the air, resulting in limited application. At the same time, their sintering density is low, resulting in an increase in the length of the ion conduction path and a decrease in conductivity.
The preparation method of reverse coated BaCe1-xGdxO3-δ@Ce1-xGdxO2-δ core-shell structure complex-phase ceramics was used to synthesize core-shell structure powders by co-precipitation method through the new (NH4)2CO3 as a precipitant, thereby improving the interface ratio of BCG/GDC and enhancing the sintering density of the material.
By constructing a core-shell structure, the sintering density of BCG@GDC complex phase ceramics is improved, the ion conduction path length is shortened, the conductivity is improved, and the reaction between BaCeO3 and H2O and CO2 is effectively prevented.
Smart Images

Figure CN119661223A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of solid electrolyte materials, and in particular to a reverse-coated BaCe 1-x G x O 3-δ @Ce 1- x G x O 2-δ Core-shell structured composite ceramics and preparation method thereof. Technical Background
[0002] CeO 2 It is an important solid electrolyte of oxygen ion conductor. Studies have found that rare earth ion or alkaline earth metal ion doped CeO 2 It has high ionic conductivity, but it has a certain electronic conductivity in a reducing atmosphere, which will cause a certain degradation of the battery performance. 2 In the electrolyte, Ce 0.8 Sm 0.2 O 1.95 (SDC) and Ce 0.9 G 0.1 O 1.95 (GDC) is considered to be the most promising solid electrolyte to replace YSZ for use in devices such as intermediate-temperature solid fuel cells (IT-SOFCs), oxygen separation membranes, and oxygen sensors.
[0003] Bc 3 BaCeO is a typical proton conductor, showing unique advantages in many fields such as solid oxide fuel cells, oxygen sensors, and catalysis. In order to improve its conductivity and stability in acidic and water vapor environments, rare earth elements are generally used to optimize its performance. 3 Proton conductor electrolytes are considered to be the most promising electrolytes to replace YSZ oxygen ion conductors. 3 In the air, it is easy to react with H 2 O and CO 2 The reaction generates Ba(OH) 2 、BaCO 3 、CeO 2 This restricts its application.
[0004] It has been reported that the preparation of BaCe 0.9 G 0.1 O 2.95 (BCG) as the shell, Ce 0.8 G 0.2 O 1.9The core-shell structure composite ceramics with (GDC) as the core, although the grain boundary conductivity of GDC is improved by constructing the core-shell structure, the sintering density of the outer shell BCG is low, which leads to the difficulty of sintering and low density of GDC@BCG core-shell structure composite ceramics, resulting in a decrease in the effective ion transmission cross-section, destroying the continuity of the material structure, and making the ions need to bypass these obstacles when conducting in the material, thereby greatly increasing the path length of ion conduction.
[0005] Therefore, by constructing a core-shell structure, increasing the ratio of the BCG / GDC two-phase interface, and forming a high-speed channel for ion transmission, the conductivity is further improved, solving the disadvantages of separation, discontinuity, and uneven distribution of the BCG and GDC two-phase interface in traditional mechanical mixing. Summary of the invention
[0006] The present invention uses a new type (NH 4 ) 2 CO 3 The powder with smaller grain size increases the ratio of BCG / GDC two-phase interface, and the core-shell structured composite ceramics are synthesized by conventional sintering.
[0007] The reverse coated BaCe 1-x G x O 3-δ @Ce 1-x G x O 2-δ The implementation scheme of the core-shell structure composite ceramics comprises the following steps:
[0008] (1) 3 COO 2 Ba、Ce(NO 3 ) 3 6H 2 O and Gd(NO 3 ) 3 6H 2 O mixed and dissolved in water, then (NH 4 ) 2 CO 3 , CH 3 (CH 2 ) 11 C 6 H 4 SO 3 Na and finally solution A is obtained;
[0009] (2)Ce(NO 3 ) 3 6H 2 O and Gd(NO 3 ) 36H 2 O is mixed and dissolved in water to obtain a precursor solution;
[0010] (3) Add the precursor solution to solution A, mix well, and then add NH 3 ·H 2 O until the precipitation is complete, ultrasonic dispersion, and polyvinyl pyrrolidone is added to stir, and washing, centrifugation, and drying are performed in sequence. The precursor powder is dried and pre-calcined to obtain a core-shell powder, and then polyvinyl alcohol is added, tableted, and sintered to obtain BaCe 1-x G x O 3-δ @Ce 1-x G x O 2-δ Core-shell structured composite ceramics.
[0011] Preferably, as an embodiment of the present invention, the step (1) (CH 3 COO 2 Ba、Ce(NO 3 ) 3 6H 2 O and Gd(NO 3 ) 3 6H 2 The molar ratio of O is 1:(0.8~0.9):(0.1~0.2).
[0012] Preferably, as an embodiment of the present invention, the step (1) uses (NH 4 ) 2 CO 3 , (CH 3 COO 2 Ba and CH 3 (CH 2 ) 11 C 6 H 4 SO 3 The molar ratio of Na is (1~1.5):1:(0.1~0.2).
[0013] Preferably, as an embodiment of the present invention, the step (2) uses Ce(NO 3 ) 3 6H 2 O and Gd(NO 3 ) 3 6H 2 The molar ratio of O is (0.8~0.9):(0.1~0.2).
[0014] Preferably, as an embodiment of the present invention, the CH used in step (3) 3 (CH2 ) 11 C 6 H 4 SO 3 Na acts as a surfactant.
[0015] Preferably, as an embodiment of the present invention, the polyvinyl pyrrolidone and (CH 3 COO 2 The molar ratio of Ba (0.3~0.4):1.
[0016] Preferably, as an embodiment of the present invention, the Ce in the precursor solution in step (2) is 3+ With Ba in solution A 2+ The molar ratio is (0.8~0.9):1.
[0017] Preferably, as an embodiment of the present invention, the stirring time in step (3) is 10 to 12 hours.
[0018] Preferably, as an embodiment of the present invention, the drying temperature in step (3) is 100 to 120° C., and the drying time is 10 to 20 hours.
[0019] Preferably, as an embodiment of the present invention, the pre-calcination temperature in step (3) is 800-900° C., and the pre-calcination time is 5-6 hours.
[0020] Preferably, as an embodiment of the present invention, the purpose of adding polyvinyl alcohol in step (3) is to achieve powder bonding and achieve better tableting effect.
[0021] Preferably, as an embodiment of the present invention, the sintering temperature in step (3) is 1500-1600° C., and the insulation time is 9-12 hours.
[0022] The reverse coated BaCe 1-x G x O 3-δ @Ce 1-x G x O 2-δ Core-shell composite ceramics using a new precipitant to synthesize a new type of (NH 4 ) 2 CO 3 The reverse coated BaCe was synthesized by coprecipitation method as a precipitant 1-x G x O 3-δ @Ce 1- x G x O 2-δCore-shell powder, combined with conventional sintering, obtains core-shell structure composite ceramics, the chemical expression is BaCe 1-x G x O 3-δ @Ce 1-x G x O 2-δ (BCG@GDC), where x = 0.1 ~ 0.2, δ = 0 ~ 0.1.
[0023] The core-shell structure of the present invention increases the interface ratio of BCG and GDC, improves the continuity of the two phases, builds a high-speed channel for ion transmission, and further improves the conductivity. Compared with the traditional mechanically mixed BCG and GDC core-shell structure, it solves the problems of separation, discontinuity, and uneven distribution of the two-phase interface. GDC coating BCG and the new precipitant work together to effectively prevent BaCeO 3 In air with H 2 O and CO 2 The reaction generates Ba(OH) 2 、BaCO 3 , hindering ion transport.
[0024] The GDC shell with better sintering density and the BCG core with poor sintering performance described in the present invention are reversely coated, which can improve the sintering density of BCG@GDC composite ceramics, making the internal structure of the high-density material more compact and regular, with relatively fewer pores, voids and defects, providing a more direct and smooth path for ion conduction. Ions can move along a relatively continuous lattice structure in the material, without having to frequently bypass a large number of pores and defects as in low-density materials, greatly shortening the path length of ion conduction.
[0025] Beneficial effects of the present invention:
[0026] (1) The core-shell structure constructed by the present invention improves the sintering density of BCG@GDC composite ceramics. The internal structure of the high-density material is more compact and regular, with relatively fewer pores, voids and defects, providing a more direct and smooth ion conduction path, without the need to frequently bypass a large number of pores and defects as in low-density materials, greatly shortening the path length of ion conduction. By constructing a core-shell structure, the BCG / GDC two-phase interface ratio is increased, the continuity of the two phases is further improved, and a high-speed channel for ion transmission is constructed to further improve the conductivity. In addition, GDC is coated on BCG, which can effectively prevent BaCeO 3 In air with H 2 O and CO 2 The reaction generates Ba(OH) 2 .
[0027] (2) In the core-shell structure constructed by the present invention, the good sintering properties of GDC can promote the growth and densification of grains during the sintering process. When GDC is coated on the surface of BCG, the GDC coating layer undergoes a certain degree of densification before BCG during the high-temperature sintering stage, forming a skeleton-like structure that provides support for the internal BCG, limits the abnormal growth of BCG grains, and effectively fills the pores between BCG grains, thereby significantly improving the sintering density of the overall material. Compared with uncoated BCG ceramics, the density can be increased by 3% to 5%, greatly improving the uniformity of the microstructure of the material.
[0028] (3) The preparation method of the present invention uses a novel (NH 4 ) 2 CO 3 As a precipitant, (NH 4 ) 2 CO 3 With (CH 3 COO 2 Ba molar ratio is 1: (1-1.5), which can obtain BaCO which is hardly soluble in water. 3 , can avoid loss during washing and centrifugation, can effectively ensure the existence of BCG and GDC phases, the preparation method is simple and the economic cost is low.
[0029] (4) The core-shell structure nanopowder prepared by the present invention has a spherical shape, which helps to build a two-phase interface and thus improve the electrical conductivity. The electrical conductivity at 600°C in air atmosphere can reach 1.07×10 -2 S / cm.
[0030] (5) The present invention constructs BaCe 1-x G x O 3-δ @Ce 1-x G x O 2-δ Core-shell structure, the interface between BCG and GDC can be used as H + and O 2- The high-speed channel improves the conductivity of the composite ceramic, and the BCG and GDC core-shell structures can also achieve a higher interface ratio, thereby improving the conductivity of the composite electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The BaCe prepared in Example 1 0.8 G 0.2 O 3-δ @Ce 0.8 G 0.2 O 2-δ XRD pattern of core-shell structure powder.
[0032] Figure 2 The BaCe prepared in Example 1 0.8 G 0.2 O 3-δ @Ce 0.8 G 0.2 O 2-δ SEM image and grain distribution diagram of core-shell structure powder, (a) is BaCe prepared in Example 1 0.8 G 0.2 O 3-δ @Ce 0.8 G 0.2 O 2-δ SEM image of core-shell structure powder; (b) is BaCe prepared in Example 1 0.8 G 0.2 O 3-δ @Ce 0.8 G 0.2 O 2-δ Normal distribution diagram of core-shell structure powder grains.
[0033] Figure 3 The BaCe prepared in Example 1 0.8 G 0.2 O 3-δ @Ce 0.8 G 0.2 O 2-δ TEM image of core-shell structure powder.
[0034] Figure 4 The BaCe prepared in Example 1 0.8 G 0.2 O 3-δ @Ce 0.8 G 0.2 O 2-δ AC impedance diagram of core-shell structured composite ceramics.
[0035] Figure 5 The BaCe prepared in Example 2 0.9 G 0.1 O 3-δ @Ce 0.9 G 0.1 O 2-δ XRD pattern of core-shell structure powder.
[0036] Figure 6 The BaCe prepared in Example 2 0.9 G 0.1 O 3-δ @Ce 0.9 G 0.1 O 2-δ SEM image and grain distribution diagram of core-shell structure powder, (a) is BaCe prepared in Example 20.9 G 0.1 O 3-δ @Ce 0.9 G 0.1 O 2-δ SEM image of core-shell structure powder; (b) is BaCe prepared in Example 2 0.9 G 0.1 O 3-δ @Ce 0.9 G 0.1 O 2-δ Gaussian curve of the core-shell structure powder grain distribution.
[0037] Figure 7 The BaCe prepared in Example 2 0.9 G 0.1 O 3-δ @Ce 0.9 G 0.1 O 2-δ TEM image of core-shell structure powder.
[0038] Figure 8 The BaCe prepared in Example 2 0.9 G 0.1 O 3-δ @Ce 0.9 G 0.1 O 2-δ AC impedance diagram of core-shell structured composite ceramics.
[0039] Fig. 9 The BaCe prepared in Comparative Example 1 0.8 G 0.2 O 3-δ @Ce 0.8 G 0.2 O 2-δ XRD pattern of core-shell structure powder.
[0040] Fig.10 The BaCe prepared in Comparative Example 1 0.8 G 0.2 O 3-δ @Ce 0.8 G 0.2 O 2-δ The SEM image and grain distribution diagram of the core-shell structure powder (a) is the BaCe prepared in Comparative Example 1. 0.8 G 0.2 O 3-δ @Ce 0.8 G 0.2 O 2-δ SEM image of core-shell structure powder; (b) BaCe prepared in Comparative Example 1 0.8 G 0.2 O 3-δ@Ce 0.8 G 0.2 O 2-δ Normal distribution diagram of grains of core-shell structure powder.
[0041] Fig.11 The BaCe prepared in Comparative Example 1 0.8 G 0.2 O 3-δ @Ce 0.8 G 0.2 O 2-δ AC impedance diagram of core-shell structured composite ceramics.
[0042] Fig.12 The BaCe prepared in Comparative Example 2 0.8 G 0.2 O 3-δ @Ce 0.8 G 0.2 O 2-δ AC impedance diagram of core-shell structured composite ceramics.
[0043] Fig.13 The BaCe prepared in Comparative Example 3 0.8 G 0.2 O 3-δ @Ce 0.8 G 0.2 O 2-δ XRD pattern of core-shell structure powder.
[0044] Fig.14 Ce obtained in Comparative Example 4 0.8 G 0.2 O 2-δ @BaCe 0.8 G 0.2 O 3-δ AC impedance diagram of core-shell ceramics.
[0045] Fig.15 The reverse coated BaCe 0.8 G 0.2 O 3-δ @Ce 0.8 G 0.2 O 2-δ Flow chart of the preparation of core-shell structured composite ceramics. DETAILED DESCRIPTION
[0046] The present invention is further described in detail below with reference to the accompanying drawings and specific implementation examples, but the protection scope of the present invention is not limited to the described contents.
[0047] Example 1
[0048] A reverse coated BaCe 0.8 G0.2 O 3-δ @Ce 0.8 G 0.2 O 2-δ The method for preparing a core-shell structure composite ceramic comprises the following steps:
[0049] (1) 0.01 mol (CH 3 COO 2 Ba, 0.008molCe(NO 3 ) 3 6H 2 O, 0.002molGd(NO 3 ) 3 6H 2 O was mixed and dissolved in 100 mL of distilled water, and 0.2 mol / L (NH 4 ) 2 CO 3 Solution, continue to slowly add 0.02mol / LCH 3 (CH 2 ) 11 C 6 H 4 SO 3 Solution A is obtained from Na solution.
[0050] (2) 0.008 molCe(NO 3 ) 3 6H 2 O, 0.002molGd(NO 3 ) 3 6H 2 O was dissolved in 100 mL of distilled water to obtain a precursor solution.
[0051] (3) Slowly drip the precursor solution into solution A, stir thoroughly, and slowly add NH 3 ·H 2 O was precipitated and fully ultrasonically dispersed, then slowly dripped into a 0.08 mol / L polyvinyl pyrrolidone solution, stirred for 10 h, washed with anhydrous ethanol, centrifuged, stirred and dried at 100 ° C for 10 h, and the final precursor powder was pre-calcined at 850 ° C for 5 h to obtain BCG@GDC core-shell structure powder, added a drop of polyvinyl alcohol binder, pressed and sintered at 1500 ° C for 9 h to obtain reverse coated BaCe 0.8 G 0.2 O 3-δ @Ce 0.8 G 0.2 O 2-δ Core-shell structured composite ceramics.
[0052] Example 2
[0053] A reverse coated BaCe 0.9 G 0.1 O 3-δ @Ce 0.9 G 0.1 O 2-δ The method for preparing a core-shell structure composite ceramic comprises the following steps:
[0054] (1) 0.01 mol (CH 3 COO 2 Ba, 0.009molCe(NO 3 ) 3 6H 2 O, 0.001molGd(NO 3 ) 3 6H 2 O was mixed and dissolved in 100 mL of distilled water, and 0.2 mol / L (NH 4 ) 2 CO 3 Solution, continue to add 0.02mol / LCH 3 (CH 2 ) 11 C 6 H 4 SO 3 Na solution to obtain solution A.
[0055] (2) 0.009 molCe(NO 3 ) 3 6H 2 O, 0.001molGd(NO 3 ) 3 6H 2 O was dissolved in 100 mL of distilled water to obtain a mixed precursor solution.
[0056] (3) Slowly drip the precursor solution into solution A, stir thoroughly, and slowly add NH 3 ·H 2 O was precipitated and fully ultrasonically dispersed, and then slowly added to a 0.08 mol / L polyvinyl pyrrolidone solution, stirred for 10 h, washed with anhydrous ethanol, centrifuged, stirred, and dried at 100 ° C for 10 h. The final precursor powder was pre-calcined at 800 ° C for 5 h to obtain BCG@GDC core-shell structure powder, and a drop of polyvinyl alcohol binder was added. After tableting, it was sintered at 1500 ° C for 9 h to obtain reverse-coated BaCe 0.9 G 0.1 O 3-δ @Ce 0.9 G 0.1 O 2-δ Core-shell structured composite ceramics.
[0057] Example 3
[0058] A reverse coated BaCe 0.8 G 0.2 O 3-δ @Ce 0.8 G 0.2 O 2-δ The method for preparing a core-shell structure composite ceramic comprises the following steps:
[0059] (1) 0.01 mol (CH 3 COO 2 Ba, 0.008molCe(NO 3 ) 3 6H 2 O, 0.002molGd(NO 3 ) 3 6H 2 O was mixed and dissolved in 100 mL of distilled water, and 0.2 mol / L (NH 4 ) 2 CO 3 Solution, slowly add 0.02mol / LCH 3 (CH 2 ) 11 C 6 H 4 SO 3 Solution A is obtained from Na solution.
[0060] (2) 0.008 molCe(NO 3 ) 3 6H 2 O, 0.002molGd(NO 3 ) 3 6H 2 O was dissolved in 100 mL of distilled water to obtain a precursor solution.
[0061] (3) Slowly drip the precursor solution into solution A, stir thoroughly, and slowly add NH 3 ·H 2 O was precipitated and fully ultrasonically dispersed, then slowly dripped into a 0.08 mol / L polyvinyl pyrrolidone solution, stirred for 10 h, washed with anhydrous ethanol, centrifuged, stirred and dried at 100 ° C for 10 h, and the final precursor powder was pre-calcined at 900 ° C for 5 h to obtain BCG@GDC core-shell structure powder, a drop of polyvinyl alcohol binder was added, and the tablet was sintered at 1500 ° C for 9 h to obtain reverse coated BaCe 0.8 G 0.2 O 3-δ @Ce 0.8 G0.2 O 2-δ Core-shell structured composite ceramics.
[0062] The BCG@GDC core-shell structure powder prepared in Example 1-2 was subjected to XRD test. Figure 1 It can be seen that the BaCe prepared in Example 1 0.8 G 0.2 O 3-δ @Ce 0.8 G 0.2 O 2-δ The core-shell structure powder XRD has no impurity phase, and the diffraction peaks of BCG and GDC can be clearly seen. The desired substance can be produced according to the predetermined design, which shows that the design of the present invention is reasonable. When the pre-calcination temperature is reduced and the Ce 3+ With Gd 3+ When the molar ratio of Figure 5 It can be seen that the BaCe prepared in Example 2 0.9 G 0.1 O 3-δ @Ce 0.9 G 0.1 O 2-δ The core-shell structure powder has mixed peaks but the diffraction peaks of BCG and GDC can be clearly seen, which shows that the design of the present invention is reasonable and can produce the required substances according to the predetermined design.
[0063] The BCG@GDC core-shell structure powder prepared in Example 1-2 was subjected to SEM analysis. Figure 2 The BaCe prepared in Example 1 is shown 0.8 G 0.2 O 3-δ @Ce 0.8 G 0.2 O 2-δ The core-shell structure powder is basically normally distributed, with an average grain size of 49nm; Figure 6 As shown, the BaCe prepared in Example 2 0.9 G 0.1 O 3-δ @Ce 0.9 G 0.1 O 2-δ The core-shell structure powder has a grain distribution according to a Gaussian curve and an average grain size of 44 nm.
[0064] The BCG@GDC core-shell structure powder prepared in Example 1-2 was subjected to TEM analysis. 0.8 G 0.2 O 3-δ @Ce 0.8 G 0.2 O2-δ The TEM analysis results of core-shell structure powder are as follows Figure 3 As shown, the lattice fringes of BCG and GDC can be clearly observed, and it can be clearly seen that BCG is coated with GDC; the BaCe prepared in Example 2 0.9 G 0.1 O 3-δ @Ce 0.9 G 0.1 O 2-δ TEM analysis results of core-shell structure powder, such as Figure 7 As shown, the lattice fringes of BCG and GDC can be clearly observed, and it can be clearly seen that BCG is wrapped by GDC.
[0065] The BCG@GDC core-shell structure ceramics prepared in Example 1-2 were subjected to an AC impedance test at 600°C in air atmosphere. The results were shown in Figure 2 based on the equivalent circuit fitting. Figure 4 As shown, the conductivity is 1.07×10 -2 S / cm; BaCe prepared in Example 2 0.9 G 0.1 O 3-δ @Ce 0.9 G 0.1 O 2-δ The core-shell composite ceramics were subjected to an AC impedance test at 600°C in air atmosphere. According to the equivalent circuit fitting, the results are as follows: Figure 8 As shown, the conductivity is 1.05×10 -2 S / cm.
[0066] The BCG@GDC core-shell structure ceramics prepared in Example 1-2 were tested for density by Archimedes drainage method, and their relative density was 95-96.2%. The conductivity and density of the BCG@GDC core-shell structure ceramics prepared in Example 3 were similar to those of the BCG@GDC core-shell structure ceramics prepared in Example 1-2.
[0067] Comparative Example 1
[0068] A reverse coated BaCe 0.8 G 0.2 O 3-δ @Ce 0.8 G 0.2 O 2-δ The preparation method of core-shell structure composite ceramics has the following specific steps:
[0069] (1) Weigh 0.01 mol (CH 3 COO 2 Ba, 0.008molCe(NO 3 ) 3 6H2 O, 0.002molGd(NO 3 ) 3 6H 2 O was dissolved in 100 mL of distilled water and NH 3 ·H 2 O until the solution pH is 8-10, and then continue to add 0.02 mol / L CH 3 (CH 2 ) 11 C 6 H 4 SO 3 Na solution to obtain solution A.
[0070] (2) Weigh 0.008 mol (Ce (NO 3 ) 3 6H 2 O, 0.002molGd(NO 3 ) 3 6H 2 O was dissolved in 100 mL of distilled water to obtain a precursor solution.
[0071] (3) Slowly drip the precursor solution into solution A and stir thoroughly. Add NH 3 ·H 2 O was precipitated and fully ultrasonically dispersed, then slowly added to a 0.08 mol / L polyvinyl pyrrolidone solution and stirred for 10 h. The obtained suspension was stirred and placed in a drying oven at 100 °C for 10 h. The obtained precursor powder was pre-calcined at 850 °C for 5 h to obtain a BCG@GDC core-shell structure powder. A drop of polyvinyl alcohol binder was added, and the tablet was pressed and sintered at 1500 °C for 9 h to obtain a reverse-coated BaCe 0.8 G 0.2 O 3-δ @Ce 0.8 G 0.2 O 2-δ Core-shell structured composite ceramics.
[0072] Comparative Example 2
[0073] A reverse coated BaCe 0.8 G 0.2 O 3-δ @Ce 0.8 G 0.2 O 2-δ The preparation method of core-shell structure composite ceramics has the following specific steps:
[0074] (1) Weigh 0.01 mol (CH 3 COO 2 Ba, 0.008molCe(NO3 ) 3 6H 2 O, 0.002molGd(NO 3 ) 3 6H 2 O was dissolved in 100 mL of distilled water and NH 3 ·H 2 O until the solution pH is 8-10, and then continue to add 0.02 mol / L CH 3 (CH 2 ) 11 C 6 H 4 SO 3 Na solution to obtain solution A.
[0075] (2) Weigh 0.008 molCe(NO 3 ) 3 6H 2 O, 0.002molGd(NO 3 ) 3 6H 2 O was dissolved in 100 mL of distilled water to obtain a precursor solution.
[0076] (3) Slowly drip the precursor solution into solution A and stir thoroughly. Add NH 3 ·H 2 After being precipitated by O and fully ultrasonically dispersed, it was slowly dripped into a 0.08 mol / L polyvinyl pyrrolidone solution and stirred for 10 h. The obtained suspension was stirred and placed in a drying oven at 100 °C for 10 h to obtain a dry precursor powder. It was further pre-calcined at 800 °C for 5 h to obtain a BCG@GDC core-shell structure powder. A drop of polyvinyl alcohol binder was added, and the tablet was pressed and sintered at 1500 °C for 9 h to obtain a reverse-coated BaCe 0.8 G 0.2 O 3-δ @Ce 0.8 G 0.2 O 2-δ Core-shell structured composite ceramics.
[0077] Comparative Example 3
[0078] A reverse coated BaCe 0.8 G 0.2 O 3-δ @Ce 0.8 G 0.2 O 2-δ The preparation method of core-shell structure ceramics has the following specific steps:
[0079] (1) Weigh 0.01 mol (CH 3 COO2 Ba, 0.008molCe(NO 3 ) 3 6H 2 O, 0.002molGd(NO 3 ) 3 6H 2 O was dissolved in 100 mL of distilled water and NH 3 ·H 2 O until the solution pH is 8-10, and then slowly add 0.02 mol / L CH 3 (CH 2 ) 11 C 6 H 4 SO 3 Na solution to obtain solution A.
[0080] (2) Weigh 0.008 molCe(NO 3 ) 3 6H 2 O, 0.002molGd(NO 3 ) 3 6H 2 O is weighed according to the stoichiometric ratio and dissolved in an appropriate amount of distilled water to obtain a precursor solution.
[0081] (3) Slowly drip the precursor solution into solution A, stir thoroughly, and add NH 3 ·H 2 O was precipitated and fully ultrasonically dispersed, then slowly dripped into a 0.08 mol / L polyvinyl pyrrolidone solution and stirred for 10 h to obtain a suspension. After washing with anhydrous ethanol, centrifuging and stirring, the suspension was placed in a drying oven at 100 °C for 10 h. The dried precursor powder was dried and calcined at 900 °C for 5 h to obtain a BCG@GDC core-shell structure powder. A drop of polyvinyl alcohol binder was added, and the tablet was pressed and sintered at 1500 °C for 9 h to obtain a reverse-coated BaCe 0.8 G 0.2 O 3-δ @Ce 0.8 G 0.2 O 2-δ Core-shell structured composite ceramics.
[0082] Comparative Example 4
[0083] A forward coated Ce 0.8 G 0.2 O 2-δ @BaCe 0.8 G 0.2 O 3-δ The preparation method of core-shell structure composite ceramics has the following specific steps:
[0084] (1) Weigh 0.01 mol (CH 3 COO 2 Ba, 0.008molCe(NO 3 ) 3 6H 2 O, 0.002molGd(NO 3 ) 3 6H 2 O was mixed and dissolved in 100 mL of distilled water to obtain a precursor solution.
[0085] (2) Weigh 0.008 molCe(NO 3 ) 3 6H 2 O, 0.002molGd(NO 3 ) 3 6H 2 O was dissolved in 100 mL of distilled water and mixed well. NH 3 ·H 2 O until the pH value of the solution is 8-10, and then continue to slowly add 0.02 mol / L CH 3 (CH 2 ) 11 C 6 H 4 SO 3 Na solution to obtain solution A.
[0086] (3) Slowly drip the precursor solution into solution A, stir thoroughly, and add NH 3 ·H 2 O was precipitated, and after sufficient ultrasonic dispersion, it was slowly dripped into a 0.08 mol / L polyvinyl pyrrolidone solution and stirred for 10 h to obtain a suspension. After stirring, it was placed in a drying oven at 100 ° C for 10 h to obtain a dried precursor powder, and then calcined at 850 ° C for 5 h to obtain a GDC@BCG core-shell structure powder. A drop of polyvinyl alcohol binder was added, and after tableting, it was sintered at 1500 ° C for 9 h to obtain a positively coated Ce 0.8 G 0.2 O 2-δ @BaCe 0.8 G 0.2 O 3-δ Core-shell structured composite ceramics.
[0087] Effect example
[0088] The BCG@GDC core-shell structure nanopowders prepared in Comparative Examples 1 and 3 were subjected to XRD test. Fig. 9 As shown, the reverse coated BaCe prepared in Comparative Example 1 0.8 G 0.2O 3-δ @Ce 0.8 G 0.2 O 2-δ Core-shell structure powder, due to the use of NH 3 ·H 2 O is used as a precipitant, and only a small amount of BCG is precipitated, making the diffraction peak of BCG in the XRD diagram weak, and the peak of BCG is almost invisible, proving that there is only a small amount of BCG in the core-shell structure powder, which is not conducive to the construction of the core-shell structure; the reverse-coated BaCe prepared in Comparative Example 3 0.8 G 0.2 O 3-δ @Ce 0.8 G 0.2 O 2-δ Core-shell structure powder, from Fig.13 It can be seen that there is only the diffraction peak of GDC, but no diffraction peak of BCG, indicating that there is only GDC in the prepared sample.
[0089] The reverse coated BaCe prepared in Comparative Example 1 0.8 G 0.2 O 3-δ @Ce 0.8 G 0.2 O 2-δ The core-shell structure powder was subjected to SEM analysis, such as Fig.10 As shown, the grains are basically normally distributed, with an average grain size of 88nm.
[0090] The positively coated Ce prepared in Comparative Example 4 0.8 G 0.2 O 2-δ @BaCe 0.8 G 0.2 O 3-δ The core-shell structure composite ceramics were tested for density by the Archimedes drainage method, and the relative density was 92%.
[0091] The core-shell composite ceramics prepared in Comparative Examples 1-4 were subjected to an AC impedance test at 600°C in air atmosphere. According to the equivalent circuit fitting, Fig.11 The reverse coated BaCe prepared in Comparative Example 1 is shown 0.8 G 0.2 O 3-δ @Ce 0.8 G 0.2 O 2-δ The conductivity of core-shell ceramics is 0.58×10 -2 S / cm; Fig.12 The reverse coated BaCe prepared in Comparative Example 2 is shown 0.8 G 0.2 O 3-δ @Ce0.8 G 0.2 O 2-δ The electrical conductivity of core-shell ceramics is 0.68×10 -2 S / cm; Fig.14 The positive coated Ce prepared in Comparative Example 4 is shown 0.8 G 0.2 O 2-δ @BaCe 0.8 G 0.2 O 3-δ The electrical conductivity of core-shell ceramics is 0.7×10 -2 S / cm; Compared with Examples 1-3, the reverse coated BaCe prepared in Comparative Example 3 0.8 G 0.2 O 3-δ @Ce 0.8 G 0.2 O 2-δ The electrical conductivity of the core-shell structure ceramics is relatively poor. By comparing Examples 1-3 with Comparative Examples 1-4, it is found that the preparation method of the present invention can indeed obtain BCG@GDC core-shell structure ceramics with higher electrical conductivity and finer grains.
[0092] By comparing Examples 1-3 with Comparative Examples 1-4, it is found that the preparation method provided by the present invention can obtain BCG and GDC phases, and is conducive to the construction of a core-shell structure, thereby obtaining BCG@GDC core-shell structure ceramics with higher electrical conductivity. 4 ) 2 CO 3 When used as a precipitant, the obtained BaCO 3 Precipitation is conducive to the precipitation of BCG phase, increasing the ratio of BCG / GDC phases, improving the continuity of the two phases, and the formed ion transmission channel further improves the conductivity. Secondly, GDC coats BCG, which improves the sintering density of BCG@GDC composite ceramics. The internal structure of high-density materials is more compact and regular, with relatively fewer pores, voids and defects. Compared with uncoated BCG ceramics, the density can be increased by 3% to 5%, greatly improving the uniformity of the microstructure of the material.
[0093] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A reverse coated BaCe 1-x G x O 3-δ @Ce 1-x G x O 2-δ The method for preparing core-shell structure composite ceramics is characterized in that: The steps include: (1) Mix (CH3COO)2Ba, Ce(NO3)3·6H2O and Gd(NO3)3·6H2O and dissolve them in water. Then add (NH4)2CO3, CH3(CH2) 11 C6H4SO3Na and then obtain solution A; (2) Ce(NO3)3·6H2O and Gd(NO3)3·6H2O are mixed and dissolved in water to obtain a precursor solution; (3) The precursor solution is added to solution A, mixed evenly, and then NH3·H2O is added until the precipitation is complete and ultrasonically dispersed, and polyvinyl pyrrolidone is added and stirred, and then washed, centrifuged, and dried in sequence. The obtained precursor powder is dried and pre-calcined to obtain a core-shell powder, and then polyvinyl alcohol is added, and tablets are pressed and sintered to obtain BaCe 1-x G x O 3-δ @Ce 1-x G x O 2-δ Core-shell structured composite ceramics, wherein x=0.1-0.2, δ=0-0.
1.
2. According to claim 1, a reverse coated BaCe 1-x G x O 3-δ @Ce 1-x G x O 2-δ The method for preparing core-shell structure composite ceramics is characterized in that: The molar ratio of (CH3COO)2Ba, Ce(NO3)3·6H2O and Gd(NO3)3·6H2O in step (1) is 1:(0.8-0.9):(0.1-0.2).
3. According to claim 1, a reverse coated BaCe 1-x G x O 3-δ @Ce 1-x G x O 2-δ The method for preparing core-shell structure composite ceramics is characterized in that: In the step (1), (NH4)2CO3, (CH3COO)2Ba and CH3(CH2) 11 The molar ratio of C6H4SO3Na is (1~1.5):1:(0.1~0.2).
4. According to claim 1, a reverse coated BaCe 1-x G x O 3-δ @Ce 1-x G x O 2-δ The method for preparing core-shell structure composite ceramics is characterized in that: The molar ratio of Ce(NO3)3·6H2O to Gd(NO3)3·6H2O in step (2) is (0.8-0.9):(0.1-0.2).
5. According to claim 1, a reverse coated BaCe 1-x G x O 3-δ @Ce 1-x G x O 2-δ The method for preparing core-shell structure composite ceramics is characterized in that: In the step (2), Ce in the precursor solution 3+ With Ba in solution A 2+ The molar ratio is (0.8~0.9):
1.
6. A reverse coated BaCe according to claim 1 1-x G x O 3-δ @Ce 1-x G x O 2-δ The method for preparing core-shell structure composite ceramics is characterized in that: In the step (3), the molar ratio of polyvinyl pyrrolidone to (CH3COO)2Ba is (0.3-0.4):
1.
7. A reverse coated BaCe according to claim 1 1-x G x O 3-δ @Ce 1-x G x O 2-δ The method for preparing core-shell structure composite ceramics is characterized in that: The pre-calcination temperature in step (3) is 800-900° C., and the pre-calcination time is 5-6 hours.
8. According to claim 1, a reverse coated BaCe 1-x G x O 3-δ @Ce 1-x G x O 2-δ The method for preparing core-shell structure composite ceramics is characterized in that: In the step (3), the sintering temperature is 1500-1600° C., and the sintering time is 9-12 hours.
9. The reverse coated BaCe according to any one of claims 1 to 8 1-x G x O 3-δ @Ce 1-x G x O 2-δ Reverse coated BaCe prepared by the preparation method of core-shell structure composite ceramics 1-x G x O 3-δ @Ce 1-x G x O 2-δ Core-shell structured composite ceramics.
Citation Information
Patent Citations
Preparation method of YDC-coated BCY dual-ion conductor ceramic with nano core-shell structure
CN118125823A
Preparation method of Ce0. 8Gd0. 2O1. 90-coated BaCe0. 9Gd0. 1O3. 95 core-shell structure nano powder
CN118645662A
Dielectric ceramic, method of manufacturing the same, and monolithic ceramic capacitor
JP2004189588A
Composite powders having core-shell structure and methods for fabricating the same
KR1020130032190A